PENGEMBANGAN VIDEO ANIMASI BERMUATAN TRI HITA KARANA PADA METERI TEKS FABEL KELAS IV SEKOLAH DASAR - Nia Charolin, Ni Komang Ameilya; Ni Made Ignityas Prima Astuti; Nyoman Ayu Putri Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Animated video media containing Tri Hita Karana on fable text material for fourth grade elementary school students was developed in this study. The basis for implementing this research is the still low conventional learning methods, lack of student motivation, the absence of character values ​​such as Tri Hita Karana and the lack of optimization of the use of digital media. This study uses a Research and Development (R&D) approach with the ADDIE model. The model consists of five systematic stages, namely the analysis stage (analyze), design (design), development (development), implementation (implement), and evaluation (evaluate). The research subjects were 30 fourth grade students of SD Negeri 1 Baler Bale Agung and teachers/homeroom teachers. Data were collected through interviews, questionnaires, and documentation. The results of the validation of material experts averaged a score of 95.93% with a